Identification and Phenotypic Characterization of Hsp90 Phosphorylation Sites That Modulate Virulence Traits in the Major Human Fungal Pathogen Candida albicans - Alaalm, Leenah; Crunden, Julia L.; Butcher, Mark; Obst, Ulrike; Whealy, Ryann; Williamson, Carolyn E.; O’Brien, Heath E.; Schaffitzel, Christiane; Ramage, Gordon; Spencer, James; Diezmann, Stephanie (Frontiers in Cellular and Infection Microbiology, 2021)
The highly conserved, ubiquitous molecular chaperone Hsp90 is a key regulator of cellular proteostasis and environmental stress responses. In human pathogenic fungi, which kill more than 1.6 million patients each year worldwide, Hsp90 governs cellular morphogenesis, drug resistance, and virulence. Yet, our understanding of the regulatory mechanisms governing fungal Hsp90 function remains sparse. Post-translational modifications are powerful components of nature’s toolbox to regulate protein abundance and function. Phosphorylation in particular is critical in many cellular signaling pathways and errant phosphorylation can have dire consequences for the cell. In the case of Hsp90, phosphorylation affects its stability and governs its interactions with co-chaperones and clients. Thereby modulating the cell’s ability to cope with environmental stress. Candida albicans, one of the leading human fungal pathogens, causes 750,000 life-threatening invasive infections worldwide with unacceptably high mortality rates. Yet, it remains unknown if and how Hsp90 phosphorylation affects C. albicans virulence traits. Here, we show that phosphorylation of Hsp90 is critical for expression of virulence traits. We combined proteomics, molecular evolution analyses and structural modeling with molecular biology to characterize the role of Hsp90 phosphorylation in this non-model pathogen. We demonstrated that phosphorylation negatively affects key virulence traits, such as the thermal stress response, morphogenesis, and drug susceptibility. Our results provide the first record of a specific Hsp90 phosphorylation site acting as modulator of fungal virulence. Post-translational modifications of Hsp90 could prove valuable in future exploitations as antifungal drug targets.